The Impact of DSO Grid-Integration Measures on EV Users in Germany - Kirstin Ganz; Patrick Vollmuth (World Electric Vehicle Journal)
As the share of electric vehicles (EVs) continues to rise, the distribution grid faces the risk of overload. In Germany, the reform of § 14a Energiewirtschaftsgesetz (German Energy Industry Act, EnWG) was introduced to address this problem. The reform has changed the revenue potential of smart chargeable uni and bidirectional EVs (smart EVs). The reform introduces variable grid fee tariffs for smart EVs, but also possible emergency power reduction measures to relieve grid overload situations. While variable grid fee tariffs can increase revenues, power reduction measures can lead to revenue losses. This work investigates the dual impact of these factors by implementing variable grid fee tariffs and the option of power reduction signals in a flexibility marketing model. Our findings indicate that smart EVs can generate significant additional revenues through variable grid fee tariffs in 2035. Conversely, the impact of emergency power signals on these revenues and the EV load profile is marginal. As a result, the effect of power reduction measures on the German load profile is also negligible.